2010
DOI: 10.1016/j.rbmo.2010.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Does early morphology provide additional selection power to blastocyst selection for transfer?

Abstract: Routine early developmental parameters are widely used in IVF centres to evaluate embryo development and fresh single-blastocyst transfer currently seems superior to single-embryo transfer. Would early morphological parameters help to choose the single blastocyst to be transferred, thereby improving the chances of implantation and live birth rate? This prospective observational study analysed the individual outcomes of 2617 embryos from 511 IVF couples scheduled for a single-blastocyst transfer. Embryo and bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 46 publications
2
25
0
2
Order By: Relevance
“…During the first days of embryo culture, morphological criteria alone are generally only weakly predictive of both embryo development and capability to procure a pregnancy [9,10]. However, currently embryos are still classified and chosen for transfer in accordance to morphological and developmental scores [11].…”
Section: Introductionmentioning
confidence: 99%
“…During the first days of embryo culture, morphological criteria alone are generally only weakly predictive of both embryo development and capability to procure a pregnancy [9,10]. However, currently embryos are still classified and chosen for transfer in accordance to morphological and developmental scores [11].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, our data showed that a good morphology on day three increases the likelihood that a blastocyst will be of good quality by up to threefold. Conversely, previous studies have suggested that the early embryo morphology is a poor predictor of the blastocyst quality in extended culture [14,15]. A recent study from Guerif et al [15] suggested that the relationship between early morphological parameters and the blastocyst morphology is weak.…”
Section: Discussionmentioning
confidence: 96%
“…Conversely, previous studies have suggested that the early embryo morphology is a poor predictor of the blastocyst quality in extended culture [14,15]. A recent study from Guerif et al [15] suggested that the relationship between early morphological parameters and the blastocyst morphology is weak. However, it was demonstrated that the degree of fragmentation on day three should be taken into account in the selection of the best blastocyst for transfer.…”
Section: Discussionmentioning
confidence: 96%
“…Dans le cadre des politiques de transfert d'un seul embryon, la culture prolongé e pré sente un inté rêt majeur [22]. L'aspect morphologique pré coce des embryons n'apporte pas d'aide à la dé cision du blastocyste à transfé rer : aucune diffé rence n'a é té observé entre les blastocystes implanté s et non implanté s selon leurs caractè res morphologiques à J2 [23,24]. On peut donc en dé duire que si la politique du centre d'AMP est la culture prolongé e systé matique, il n'est pas utile d'observer les embryons aux stades J2/J3.…”
Section: Aux Deuxie`me Et Troisie`me Jours Post Ponction (Stade J2/j3)unclassified